Changes in lung volumes and gas trapping in patients with large hiatal hernia. (22nd May 2015) - Naoum, Christopher; Kritharides, Leonard; Ing, Alvin; Falk, Gregory L.; Yiannikas, John
Abstract: Background and Aims: Studies assessing hiatal hernia (HH)‐related effects on lung volumes derived by body plethysmography are limited. We aimed to evaluate the effect of hernia size on lung volumes (including assessment by body plethysmography) and the relationship to functional capacity, as well as the impact of corrective surgery. Methods: Seventy‐three patients (70 ± 10 years; 54 female) with large HH [mean ± standard deviation, intra‐thoracic stomach (ITS) (%): 63 ± 20%; type III in 65/73] had respiratory function data (spirometry, 73/73; body plethysmography, 64/73; diffusing capacity, 71/73) and underwent HH surgery. Respiratory function was analysed in relation to hernia size (groups I, II and III: ≤50, 50%–75% and ≥75% ITS, respectively) and functional capacity. Post‐operative changes were quantified in a subgroup. Results: Total lung capacity (TLC) and vital capacity (VC) correlated inversely with hernia size (TLC: 97 ± 11%, 96 ± 13%, 88 ± 10% predicted in groups I, II and III, respectively, P = 0.01; VC: 110 ± 17%, 111 ± 14%, 98 ± 14% predicted, P = 0.02); however, mean values were normal and only 14% had abnormal lung volumes. Surgery increased TLC (93 ± 11% vs 97 ± 10% predicted) and VC (105 ± 15% vs 116 ± 18%), and decreased residual volume/total lung capacity (RV/TLC) ratio (39 ± 7% vs 37 ± 6%) ( P < 0.01 for all). Respiratory changes were modest relative to the marked functional class improvement. Among parameters that improved following HH surgery, decreased TLC and forced expiratory volume in 1 s and increased RV/TLC ratio correlated with poorer functional class pre‐operatively. Conclusions: Increasing HH size correlates with reduced TLC and VC. Surgery improves lung volumes and gas trapping; however, the changes are mild and within the normal range.